Effect of an Educational-Supportive Program Based on Roy Adaptation Model on Marital Satisfaction in Mastectomy Patients Receiving Chemotherapy - Samira Shahed; Zohreh Vanaki; Mamak Tahmasebi (Mashhad University of Medical Sciences, 2016)
Background: Regarding nurses' significant role in improving quality of marital life in mastectomy patients and their families, implication of the adaptation model can help nurses reaching this goal. Aim: This study aimed to determine Effect of an educational-supportive program based on Roy This quasi-experimental study was performed on 69 mastectomy patients receiving chemotherapy in 2013 in clinical services in Tehran, Iran. The samples were randomly allocated to two groups. The data collection instrument was ENRICH Marital Satisfaction scale (2011). In the experimental group, maladaptive behaviors and their stimuli were determined by the questionnaire, and then adaptive strategies were implemented in 45 days. The program was based on support (patients instruction), peer group, weblog, meeting with the participants' spouses, and three-month follow-up using behaviors checklist. Control group patients received the regular treatment sessions. T-test, Pearson's correlation coefficient, Spearman's rank correlation coefficient, and Chi-square tests were run, using SPSS version 19. Results: In experimental group, paired sample t-test reflected an increase in marital satisfaction from 24.7±2.6 before to 32.9±3.5 after the intervention (P=0.03). However, no significant differences were observed in the control group from 26/7±4/6 before to 26/5±4/8 after the intervention in this regard (P=0/63).   Implications for Practice: Roy Adaptation Model can be used as a framework for designing educational-supportive programs to improve quality of marital life in mastectomy patients receiving chemotherapy.